The Effectiveness of FRESH Technique to Teach Descriptive Paragraph - Faisal Faisal; Krisna Suwandita (Journal of Education and Learning (EduLearn), 2013)
This study was aimed at knowing the effectiveness of FRESH technique in teaching descriptive paragraph. The method of this study was quasi experimental method. This study was conducted at one of the state madrasah aliyah in academic year 2012/2013. The total sample of this study was 78 respondents divided into two groups: the control class with no treatment and the experimental class with FRESH technique. The data collection technique used essay tests for pre-test and post-test. The evaluation covered content, organization, vocabulary, style, and mechanic. After data analyses, the students in the experimental class had better achievement than those in the control class. The result of t-test computation was 1.968, with t-table value = 1.664 at the significant level Î± = 0.05. The t-test result was higher than the value of t-table (1.968 more than 1.664). It meant that the hypothesis was accepted or FRESH technique was effective in teaching descriptive paragraph to the students of that school in academic year 2012/2013.